Strateško nakupno vedenje - Kos Koklič, Mateja (Teorija in praksa, 2008)
The aim of this study is to apply the existing knowledge in the field of consumer behaviour to strategic consumer buying behaviour, such as home purchase, by developing and empirically testing a conceptual model. The results of our qualitative research suggest that cognitive and rational factors do not offer sufficient explanation of consumer behaviour in the case of a high-involvement product such as a house. In addition to the idiosyncratic characteristics of the customer, his/her personal situation and environmental factors, the role of feelings, experience, subconscious factors, needs and goals should to be taken into account.
Keywords: Consumers; Potrošniki; Consumer behavior; Vedenje potrošnikov; Qualitative research; Kvalitativno raziskovanje; nakup; nakupno obnašanje; raziskave